2016
DOI: 10.1177/2167702616645777
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Inflammatory Index and Recurrence of Depressive Symptoms

Abstract: There is a growing interest in understanding the role of inflammation in diet–depression relationship. The present study examined whether the dietary inflammatory index (DII, a measure of the inflammatory potential of individuals' diets) is associated with recurrent depressive symptoms (DepS) (CES-D score>16 or taking antidepressants both at baseline and follow-up) assessed over 5 years in middle-aged men (n=3178) and women (n=1068) from the Whitehall II Study. For each increment of 1 SD of DII score, odds of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 43 publications
3
69
2
4
Order By: Relevance
“…For example, the median DII score for the most pro-inflammatory quintile in NHANES is 2.39 compared to 0.66 for the same quintile in the SUN cohort, suggesting a greater inflammatory potential among Western diets compared to Mediterranean diets. The range of DII scores observed in NHANES (−5.29 to 4.71) is comparable to other American and European population-based studies, including White and Hispanic adults in the Seasonal Variation in Blood Lipids Study ( 5.3 to 4.3), 46 a cohort of British adults in Whitehall II (−3.35 to 4.23), 47 and adults in the Observation of Cardiovascular Risk Factors in Luxembourg study ( 4.02 to 4.00). 48 The range of possible DII score values do not exceed −8.87 to 7.98.…”
Section: Discussionsupporting
confidence: 81%
“…For example, the median DII score for the most pro-inflammatory quintile in NHANES is 2.39 compared to 0.66 for the same quintile in the SUN cohort, suggesting a greater inflammatory potential among Western diets compared to Mediterranean diets. The range of DII scores observed in NHANES (−5.29 to 4.71) is comparable to other American and European population-based studies, including White and Hispanic adults in the Seasonal Variation in Blood Lipids Study ( 5.3 to 4.3), 46 a cohort of British adults in Whitehall II (−3.35 to 4.23), 47 and adults in the Observation of Cardiovascular Risk Factors in Luxembourg study ( 4.02 to 4.00). 48 The range of possible DII score values do not exceed −8.87 to 7.98.…”
Section: Discussionsupporting
confidence: 81%
“…Health behaviours included smoking (classified as "current smoker" or "noncurrent smoker" (including former smokers)), alcohol consumption (classified as "no alcohol consumption in the previous week", "moderate alcohol consumption" (1-14 units/week in women and 1-21 units/week in men), and "heavy drinkers" (15 + units in women and 21 + units in men)), total energy intake (estimated from the FFQ) and physical activity (classified as "active" (> 2.5 h per week of moderate physical activity or > 1 h per week of vigorous physical activity), "inactive" (< 1 h per week of moderate physical activity and < 1 h per week of vigorous physical activity), or "moderately active" (if neither active nor inactive)) [24]. Details about the collection of this data are to be found elsewhere [25].…”
Section: Covariates Assessed In 2002/2004mentioning
confidence: 99%
“…Almudena Sánchez-Villegas et al also determined that a pro-in ammatory diet was associated with a signi cantly higher risk of depression in a Mediterranean population, particularly in older subjects [26]. Tasnime N. Akbaraly et al found that a pro-in ammatory diet was associated with recurrent depression in women, which seems not to be driven by circulating in ammatory markers [27]. There is considerable evidence that has suggested a better quality of diet or anti-in ammatory diet is associated with better quality of life and better mental health.…”
Section: Discussionmentioning
confidence: 98%